STUDI KANDUNGAN MERKURI DAN ARSEN DALAM AIR LAUT DAN SEDIMEN DI PERAIRAN TELUK BUYAT DAN RATATOTOK - Arum Prajanti; Dyah Aprianti; RTM Sutamiharja (Pusat Standardisasi Instrumen Kualitas Lingkungan Hidup Laboratorium Lingkungan (P3KLL), 2009)
Gold mining activities has been widely recognized using mercury in traditional way and using cyanide in the modernway for fixing (setting) the gold. Usually the gold is fixed with other metals such as arsenic and mercury which arethrown away as a waste. The waste from the gold mining process was thrown away through tailing pipe to the bottomof Buyat Bay and from the gold mining traditional activities are dumped to the river which ended at the RatatotokBay. The aim of this study was eager to know the mercury and arsenic content in the sea water and sediments ofthe Buyat and Ratatotok Bay, and to know the impact of these wastes to the biotic life of Buyat and Ratatotok Bay.This study was done in the period of January to March 2005, during west monsoon. The results indicated that themercury and arsenic content of the sea water quality still below the requirement of Ministry Decree of sea waterquality standard No. 51/MENLH/2004. On the contrary, the mercury content in the sediment of tailing zone andsome areas in Buyat and Ratatotok Bay are indicated as polluted sediment refer to the Guidelines Asean Marine2004. Moreover, the content of arsenic in the tailing zone, and some areas in the Buyat bay are already categorizedas polluted sediment. The arsenic and mercury content in the sea sediment deteriorating the life of sea biota, and itcan be seen from the decreasing of the benthic index diversity.